Quantitative age grading of mosquitoes using surface‐enhanced Raman spectroscopy. Issue 1 (19th November 2021) - Wang, Danhui; Yang, Jason; Pandya, Janam; Clark, John M.; Harrington, Laura C.; Murdock, Courtney C.; He, Lili
Abstract: Mosquito‐borne pathogens, including malaria, Zika, dengue, and chikungunya continue to be a major public health concern globally. Based on the understanding that only older female mosquitoes are infectious and represent a risk to human health, scientists have sought to age‐grade mosquitoes for decades. To date, however, no reliable, cost‐effective and practical methods exist to age older mosquitoes despite the tremendous epidemiological value of this approach. This study is the first attempt to develop a surface‐enhanced Raman spectroscopic (SERS) method to age mosquitoes. The water extracts of Aedes aegypti mosquitoes aged 0–22 days were mixed with silver nanoparticles. The SERS spectra, which were analysed by principal component analysis and partial least square (PLS), demonstrated the capability of this approach to predict the calendar age of mosquitoes between 0 and 22 days with the coefficient of correlation ( R ) = 0.994 and 0.990 for PLS model calibration and validation, respectively. Spectral analysis with both SERS and infrared spectroscopy revealed the key biological sources leading to changes in spectra allowing mosquito age‐grading is adenine‐containing compounds and proteins. In addition, we evaluated the impact of two arthropod‐borne pathogen deactivating pre‐treatments (bleach and ethanol) on the discrimination capability of the SERS approach. The result shows the ethanol treatment has the potential to enhance the discrimination capability and the safety of the approach. This study represents the first step towards developing the SERS approach as a quick, reliable and field‐deployable method for mosquito age‐grading, which would significantly improve the effectiveness of vector‐borne disease monitoring and prevention.